Evolution characteristics and causes of iodine and fluoride in groundwater of Hengshui city in North China - Yapeng Tuo; Baizhong Yan; Junbai Gai; Yanbo Yu; Xinkai Zhan; Yuanjing Zhang; Shuwei Qiu (Scientific Reports)
Abstract Iodine and fluoride are essential trace elements for human health, with both deficiency and excess intake impacting well-being. This study investigates the groundwater funnel area in eastern Hengshui City, utilizing groundwater level and hydrochemical data from 2014 to 2022. Hydrogeochemical methods were employed to comprehensively analyze the evolution characteristics and causes of iodine and fluoride concentrations in the funnel area. The results show: (1) After the implementation of groundwater exploitation reduction (GER) (post-2014), the mean concentration of I⁻ in the study area’s shallow groundwater (SG) decreased from 0.17 mg/L to 0.16 mg/L. Conversely, the mean concentration of F⁻ increased from 1.00 mg/L to 1.12 mg/L. In the deep groundwater (DG), the mean concentration of I⁻ rose from 0.17 mg/L to 0.19 mg/L, and the mean concentration of F⁻ increased from 1.99 mg/L to 2.90 mg/L. (2) In 2014, the concentrations of I⁻ and F⁻ in SG increased progressively from the recharge area to the discharge area along the groundwater flow. By 2018 and 2022, the concentrations of I⁻ and F⁻ in the recharge area had become higher than those in the discharge area. Between 2014 and 2022, the concentrations of I⁻ and F⁻ in DG progressively increased from the recharge area to the discharge area along the groundwater flow. (3) Before and after GER, the primary sources of I⁻ and F⁻ in both SG and DG remained consistent. Nevertheless, prolonged GER and recharge have altered the groundwater hydraulic conditions, pH, redox environment, HCO₃⁻ concentration, Ca2+ concentration, and cation exchange processes. These changes have led to the evolution of I⁻ and F⁻ concentrations.